Inclusão de grãos de milho avariados na alimentação de frangos de corte de 1 a 42 dias de idade - Silva, Awanne Elize Pinto (2020)
The objective of this study was to evaluate the impact of the damaged corn grain content in the feed of broilers from 1 to 42 days old. 540 broiler chicks of the Cobb® line were used, distributed in a completely randomized design, with five treatments and six replications of 18 birds each. The treatments consisted of five levels of inclusion of damaged corn grains (0, 25, 50, 75, 100%) replacing corn without damage. Performance, carcass characteristics, intestinal morphometry and blood parameters were evaluated. Feed intake (CR) and weight gain (GP) of broilers varied quadratically, depending on the levels of damaged corn kernels, increasing to the estimated level of 32.33% and 28.50% respectively. There was no significant effect on feed conversion. There was a quadratic effect for the thigh yield of chickens fed with damaged corn levels, increasing to the estimated level of 33%. There was an increasing linear effect for back yield. The levels of damaged maize grains added to the feed did not significantly influence the yields of carcass, breast, drumstick, wing and percentage of fat. The eosinophil rates showed a quadratic behavior, depending on the levels of damaged corn grains, increasing to the estimated levels of 48.83%, no significant effects were observed on the levels of total leukocytes, heterophiles, lymphocytes, monocytes and total plasma proteins. There was a quadratic effect on the blood globulin content and on the albumin / globulin ratio, with levels estimated at 37.50% and 41.67%, respectively. A decreasing linear effect was observed for the activities of the enzymes creatine kinase (CK) and aspartate aminotransferase (AST) and there was no significant effect on the levels of uric acid, urea, total protein and albumin. There was a quadratic effect for villus height in the portion of the ileum at the level of 44.21% of damaged corn and an increasing linear effect for crypt depth in the portion of the duodenum and ileum. It is concluded that the inclusion of up to 28.50% of damaged corn kernels provided better results for weight gain in broilers from 01 to 42 days of age.